Chemical constituents from the flower of Macaranga triloba / Ishak Zakaria @ Ali - Zakaria @ Ali, Ishak (2011)
In the present work, phytochemical study was conducted on M. triloba collected from Pasir Raja, Terengganu with the aim of isolating and identifying the flavonoids constituents from the flower of the plant. The phytochemical procedures adopted were vacuum liquid chromatography followed by column chromatography, medium pressure liquid chromatography, radial chromatography and preparative thin layer chromatography. The structural elucidation was accomplished by spectroscopic methods such as 1D-NMR (!H, 13C, DEPT), 2D-NMR (COSY, HMQC, HMBC), UV, IR and MS and comparison with published data. Isolation and purification of the flower of M. triloba afforded seven compounds comprising of five flavonoids that are 6-prenyl-3'-methoxy-eriodictyol, nymphaeol-B, flavonoid DL 4, nymphaeol-C and 6-farnesyl-3',4',5,7-tetrahydroxyflavanone and two coumarins that are 5,7- dihydroxycoumarin and scopoletin. Three flavonoids, 6-prenyl-3'-methoxyeriodictyol, flavonoid DL4 and 6-farnesyl-3',4',5,7-tetrahydroxyflavanone were isolated for the first time from Macaranga genus. 6-Prenyl-3'-methoxy-eriodictyol, nymphaeol-B, nymphaeol-C and 6-farnesyl-3',4',5,7-tetrahydroxyflavanone were tested for antioxidant, cytotoxic and antiplasmodial activity. The antioxidant activities were evaluated using the ferric thiocyanate (FTC) and thiobarbituric acid (TBA) method while the radical scavenging activity was measured by the 1,1- diphenylpicryl hydrazyl (DPPH). In FTC assay, the four flavonoids demonstrated high percent of inhibition with range of 98-100% while in TBA the percent of inhibition is slightly reduced to 81-92%. The DPPH test showed 6-farnesyl-3',4',5,7- tetrahydroxyflavanone had strong radical-scavenging activity with IC50 values of 12.2 (ig/ml followed by nymphaeol-B (13.5 ug/ml) and nymphaeol-C (16.5 ug/ml) while 6-prenyl-3'-methoxy-eriodictyol is a weak radical scavenger (155 fig/ml). The four flavonoids were also tested for cytotoxic activity against three cancer cell lines namely HeLa, HL60 and MCF-7. Three flavonoids showed significant cytotoxicity in the range 11.6 - 23.5 ug/ml. 6-Farnesyl-3',4',5,7-tetrahydroxyflavanone inhibited strongly the growth of HeLa, HL60 and MCF-7 cancer cell lines with IC50 values of 1.3 ug/ml, 3.3 ug/ml and 5.6 ug/ml respectively. Finally, for the antiplasmodial activity, 6-farnesyl-3',4',5,7-tetrahydroxyflavanone displayed the strongest inhibition activity with an IC50 value of 0.06 uM followed by nymphaeol-C and nymphaeol-B with the values of 2.04 uM and 4.02 uM. The results of these test indicated that 6- farnesyl-3',4',5,7-tetrahydoxyflavanone showed strong activities against antioxidant, cytotoxic and antiplasmodial suggesting the potential of this compound as cure for anticancer and antiplasmodial.